Leveraging videos and community health workers to address social determinants of health in immigrants (LINK-IT): Protocol for a randomized controlled trial - Lu Hu; Jing Liu; Ximin Yang; Crystal Teng; Huilin Li; Yanan Zhao; Natalie Levy; Kelly Zhu; Suzanne Vang; Simona C. Kwon; Naumi Feldman; Jennifer Lau; et al. (PLoS ONE, 2026)
Background Chinese immigrants face numerous social determinants of health (SDOH) challenges that limit access to evidence-based diabetes self-management education and support programs (DSMES). To address these challenges, our team developed the LINK-IT intervention. This manuscript presents the study protocol for the LINK-IT trial. Methods The LINK-IT trial is a 12-month, 3-arm randomized controlled trial aiming to enroll 405 Chinese immigrants with T2D (HbA1c≥7%) from multiple community and clinical settings in New York City. A total of 405 participants will be randomly allocated to one of three groups (n = 135 per group): (1) video-based DSMES plus community health worker (CHW) support (VIDEO+CHW), (2) video-based DSMES only (VIDEO), or (3) wait-list control (CONTROL). The VIDEO+CHW group will receive 24 culturally and linguistically tailored DSMES videos (one per week for 24 weeks) delivered via text message links, along with biweekly (every other week) phone calls from trained CHWs to review video content, support goal setting, and address SDOH barriers. The VIDEO group will receive the same video intervention without CHW support. The CONTROL group will receive usual care and will be offered access to the videos upon study completion. The primary outcome is the change in HbA1c at 6 months. Secondary outcomes include changes in HbA1c at 12 months, self-efficacy for diabetes, dietary intake, physical activity, medication adherence and emotional support at 6 and 12 months. Data will be analyzed using an intention-to-treat approach with linear mixed-effects models. Ethics and Dissemination This study protocol has been approved by the Institutional Review Board of the NYU Grossman School of Medicine (S23-01274). All study procedures will adhere to the ethical principles outlined in the Declaration of Helsinki. Written or verbal informed consent will be obtained from all participants. Study results will be disseminated through peer-reviewed publications, presentations at scientific conferences, and community events. Trial registration The LINK-IT trial was registered on March 20, 2024, on ClinicalTrials.gov under the identifier NCT06319716; https://clinicaltrials.gov/study/NCT06319716 .